THE IMPACT OF PHYSICAL EDUCATION ON THE MOTOR DEVELOPMENT OF STUDENTS OF A UMEI FROM VILA VELHA (Fiep Bulletin - online, 2011)
p> Discusses the contribution of Physical Education, under the perspective of the Pedagogy of Projects, of children´s motor ability development in a Primary Education. This is a co-operative action research -based work in which both researchers and teachers built knowledge and activities for a pedagogical action. The study uses motor ability tests to verify the impact of Physical Education on the motor ability development of the analyzed subjects. The results showed that pedagogical intervention contributed to the children´s motor ability development and that the lack of time for collective planning limits work according to the perspective of the Pedagogy of Projects.
Keywords: Primary Education; Motor Ability Development; Pedagogy of Projects